Ameliorative Effects of Hydromethanolic Extract of Citrullus lanatus (Watermelon) Rind on Semen Parameters, Reproductive Hormones and Testicular Oxidative Status Following Nicotine Administration in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2019)
Summary: The present study examines the possible ameliorative effects of the hydromethanolic extract of Citrullus lanatus rind (HECL) on some reproductive function and oxidative indices of the testes in male Wistar rats following administration of nicotine. Twenty male rats were assigned into four groups: Group A to D of five rats each. Group A served as control and received 2ml/kg body weight of 10% extract vehicle; Group B received 1mg/kg body weight of nicotine; Group C were co-administered 1mg/kg body weight nicotine and 500 mg/kg body weight of HECL and Group D received only 500mg/kg body weight of HECL. The drugs and extracts were administered orally to the rats for 42days; blood samples were collected by direct cardiac puncture for determination of serum concentrations of testosterone, Follicle Stimulating Hormone and Luteinizing Hormone. The testes were also harvested for determination of semen parameters: motility, morphology, viability and count and testicular tissue processed for superoxide dismutase and malondialdehyde concentration. Compared to Group A control rats, administration of HECL significantly increased sperm count and reproductive hormone concentrations amongst Group B rats (p